Patogeneza zmętnienia torebki tylnej soczewki w pseudofakii - Łukaszewska-Smyk, Agnieszka; Kałużny, Józef (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The lens epithelial cells of A and E type are involved in pathogenesis of posterior capsule opacification (PCO). They undergo metaplasia into microfibroblasts, then migrate towards posterior capsule where they proliferate and form opacification. These processes are stimulated by cytokines and interleukines. The extracellular matrix which constitutes a scaffold for migration and attachment of epithelial cells plays an important role in PCO formation. Integrines intercede in this process.